2021
DOI: 10.3390/molecules26154483
|View full text |Cite
|
Sign up to set email alerts
|

Cell Membrane-Coated Halloysite Nanotubes for Target-Specific Nanocarrier for Cancer Phototherapy

Abstract: Naturally-occurring halloysite nanotubes (HNTs) have many advantages for constructing target-specific delivery of phototherapeutic agents. Here, HNTs were labeled with fluorescein isothiocyanate (FITC) and loaded with the type-II photosensitizer indocyanine green (ICG) for phototherapy. HNTs-FITC-ICG was structurally stable due to presence of HNTs as the nanocarrier and protective agent. The nanocarrier was further wrapped with red blood cell membrane (RBCM) to enhance the biocompatibility. The HNTs-FITC-ICG-R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 49 publications
1
6
0
Order By: Relevance
“…PTT mediated by membrane-wrapped NPs is rapidly developing as a standalone therapy for solid-tumor cancers because it offers precise tumor ablation. Various kinds of NPs (e.g., nanoshells [44], nanorods [43], nanocages [46], and dye-loaded polymer NPs [91]) have been wrapped with different types of cell membranes (e.g., those derived from macrophages [44,69], RBCs [46,89], or cancer cells [60,73]) to improve their intratumoral accumulation and photothermal effect. When evaluated in murine models, these membrane-wrapped NPs have generally exhibited prolonged circulation, improved tumor delivery, and better PTT effects than their unwrapped or PEG-coated counterparts [43,44,46,60,69,85,89,91].…”
Section: Membrane-wrapped Nps For Ptt As a Standalone Therapymentioning
confidence: 99%
See 2 more Smart Citations
“…PTT mediated by membrane-wrapped NPs is rapidly developing as a standalone therapy for solid-tumor cancers because it offers precise tumor ablation. Various kinds of NPs (e.g., nanoshells [44], nanorods [43], nanocages [46], and dye-loaded polymer NPs [91]) have been wrapped with different types of cell membranes (e.g., those derived from macrophages [44,69], RBCs [46,89], or cancer cells [60,73]) to improve their intratumoral accumulation and photothermal effect. When evaluated in murine models, these membrane-wrapped NPs have generally exhibited prolonged circulation, improved tumor delivery, and better PTT effects than their unwrapped or PEG-coated counterparts [43,44,46,60,69,85,89,91].…”
Section: Membrane-wrapped Nps For Ptt As a Standalone Therapymentioning
confidence: 99%
“…Beyond gold-based NPs, other materials have been used to enable PTT including polymer-based NPs [85], mesoporous silica loaded with IR780 [91], liposomes loaded with ICG [73], metal bismuth NPs [60], inorganic magnetic iron oxide NPs [69], and inorganic halloysite nanotubes loaded with ICG [89]. The ability to wrap such materials with cell-derived membranes for enhanced PTT has shown great promise.…”
Section: Membrane-wrapped Nps For Ptt As a Standalone Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, anti-EpCAM was conjugated with HNTs-FITC-ICG-RBCM with the assistance of streptavidin to improve the specific uptake of breast cancer cells. The cell viability assay results for MCF-7 cells indicated that the HNTs-FITC-ICG-RBCM cytotoxicity was irradiation time and concentration dependent and that this could be potentially used in breast cancer treatment [ 147 ]. As evidenced by Lisuzzo et al, HNTs are excellent candidates as interfacially active inorganic particles for the formation of Pickering emulsions thanks to their advantages, as for example low cost, biocompatibility, mechanical strength, tubular morphology, etc.…”
Section: Halloysite Nanotube Application In Drug Deliverymentioning
confidence: 99%
“…Consequently, HNTs have emerged as a prominent nanomaterial for various biomedical applications, including tableting [ 25 ], drug delivery [ 22 , 26 , 27 , 28 , 29 ], tissue engineering [ 27 ], bioimaging [ 30 , 31 ], anti-cancer therapy [ 32 , 33 ], and antimicrobial solutions [ 34 ]. The latter three have been often realized by utilizing HNTs as ‘mothership’ carriers for cargoes ranging from quantum dots [ 35 , 36 ] through metal oxides NPs to precious metals [ 19 , 34 ], including gold [ 37 , 38 , 39 , 40 , 41 ].…”
Section: Introductionmentioning
confidence: 99%